Нова знахідка Leucoagaricus wichanskyi (Pilat) Bon et Boiffard для степової зони України - Ткаченко, Ф.П.; Попова, О.М.; Бабенко, О.А. (Український ботанічний журнал, 2011)
Представлены сведения о редком виде макромицета Leucoagaricus wichanskyi (Pilát) Bon et Boiffard, выявленном в степной зоне Украины. Даны характеристика его экотопа и список сопутствующих видов грибов. A rare mushroom, Leucoagaricus wichanskyi (Pilát) Bon et Boiffard, is recorded for the first time in the steppe zone of Ukraine. The habitat is characterized and list of accompanying mushroom species is given.